2013
DOI: 10.1186/1471-2407-13-132
|View full text |Cite
|
Sign up to set email alerts
|

A word of caution: do not wake sleeping dogs; micrometastases of melanoma suddenly grew after progesterone treatment

Abstract: BackgroundHormonal treatment might affect the immune response to tumor antigens induced in cancer patients who are being vaccinated.Case presentationA 33 years-old woman was diagnosed with cutaneous melanoma in May 2009. Her melanoma was located in the intermammary sulcus, had a Breslow thickness of 4 mm, a Clark’s level IV, it was ulcerated and highly melanotic. The bilateral sentinel node biopsy was negative. She entered into a randomized Phase II/III clinical study comparing a vaccine composed of irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…According to Nurses’ Health Study, the risk to developing melanoma is two times higher among women that have used oral contraception for 10 years or more [ 43 ]. It was also reported that the use of progesterone alone actuated the growth of melanoma micro-metastases [ 44 ]. Another study revealed that only low doses of progesterone (up to 1 µM), similar to the ones used in therapy, are able to stimulate melanoma cell proliferation, while higher doses not only lack such effect but even induce cell cycle arrest and apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Nurses’ Health Study, the risk to developing melanoma is two times higher among women that have used oral contraception for 10 years or more [ 43 ]. It was also reported that the use of progesterone alone actuated the growth of melanoma micro-metastases [ 44 ]. Another study revealed that only low doses of progesterone (up to 1 µM), similar to the ones used in therapy, are able to stimulate melanoma cell proliferation, while higher doses not only lack such effect but even induce cell cycle arrest and apoptosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As progesterone promotes a tolerant state in pregnancy, treating a stable melanoma patient with progesterone was found to cause proliferation of dormant micrometastases by tipping the immune system back to a Th2 state. 185 B7-H1 (PD-L1), is a molecule expressed on antigen presenting cells and contributes to tumor evasion and expansion of Tregs. 186,187 In a B7-H1 knockout mouse model of melanoma, it was discovered that females had superior tumor growth resistance compared to males due to estrogen mediated suppression of Treg cells.…”
Section: Reversing Tolerance In Melanomamentioning
confidence: 99%
“…Others larger multivariate analyses, however, demonstrated that it was equally strong in pre-as well as in post-menopausal groups [20]. Parallely, the literature concerning melanoma progression in pregnancy is also controversial [21][22][23][24], although several recent reports demonstrate that pregnancyassociated melanomas have poorer outcomes than other melanomas [25][26][27][28][29].In vitro progesterone influences melanoma growth [30][31][32][33], but several melanoma cell lines have been studied and very different experimental protocols have been used, so that the results actually available in literature are not univocal. Further research on this topic is thus needed, especially in view of the widespread use of PG in clinical practice.…”
mentioning
confidence: 97%
“…In vitro progesterone influences melanoma growth [30][31][32][33], but several melanoma cell lines have been studied and very different experimental protocols have been used, so that the results actually available in literature are not univocal. Further research on this topic is thus needed, especially in view of the widespread use of PG in clinical practice.…”
Section: Introductionmentioning
confidence: 99%